Community Empowerment: Improving Human Resource by Training Program for the Utilization of Palm Tree Raw Materials in Dayeuhkolot, Subang Regency - Nadhira Faladiba, Muthia; Wachidah, Lisnur; Kurniati, Eti; Herlina, Marizsa; Zulfita, Novaida; Putri Dwi Drajati, Karina (KnE Social Sciences, 2023)
Dayeuhkolot is one of the villages in Subang Regency which has tourism potential, such as go’ong waterfall, offroad rides, etc. In the first program in 2021, 150 sugar palm trees were planted in Dayeuhkolot, making it the village with the most palm trees in Subang Regency. Based on information from local stakeholders, the utilization of palm trees so far has not been maximized because people only focus on palm sugar products. Therefore, the author proposes a Community Empowerment program with training on the use of palm trees to become a selling value product. This training program aims to increase public knowledge regarding products that can be produced from palm trees, and have high economic value. This study aims to analyze the impact of the palm tree utilization training program on people’s knowledge of the types of products that can be produced from palm trees and the effectiveness of the training method on the use of oil palm in the community. The first method is using a live demonstration and the second is by showing a video tutorial. The study was conducted in Dayeuhkolot, Subang Regency, and consisted of 12 respondents. The analysis method used paired sample T-test and independent sample T-test. Based on research, the training program has had a positive and significant impact on increasing people’s knowledge about various products derived from palm trees and there is a difference in the average effectiveness of the training method between the direct demonstration method and the video tutorial method. Keywords: palm tree utilization, paired sample T-test, independent sample T-test, community empowerment